The role of fatty acids and lipid inflammatory mediators in the development of small airway dysfunction in asthma complicated with obesity - A. V. Yurenko; T. P. Novgorodtseva; Yu. K. Denisenko; M. V. Antonyuk; E. E. Mineeva (Acta Biomedica Scientifica, 2023)
Background. Small airway involvement is important in determining the phenotypes of bronchial asthma. Establishing the mechanisms of dysfunction of small airways will make it possible to predict the course and control bronchial asthma.The aim. To study the relationship between the modification of the composition of fatty acids, lipid inflammatory mediators (eicosanoids, plasmalogens) and the functional state of small airways and to identify lipid biomarkers for the development of small airway dysfunction in bronchial asthma associated with obesity.Materials and methods. The study included 85 patients with mild, partially controlled asthma. Of these, 39 patients with normal body weight (Group 1) and 46 patients with grade 1–2 obesity (Group 2). The control group consisted of 30 healthy volunteers. The function of the small airways was assessed according to spirometry and body plethysmography. The composition of fatty acids and plasmalogens in blood plasma was assessed by gas chromatography-mass spectrometry. In the blood serum, the content of thromboxane B2 and leukotriene B4 was determined. Statistical processing was performed using the Statistica 6.1 program (StatSoft Inc., USA). Relationships between pairs of traits were examined using the Spearman correlation test (r). Differences were considered statistically significant at p < 0.05.Results. In the combined course of asthma and obesity, dysfunction of the small airways develops against the background of generalized bronchial obstruction. A violation of lipid metabolism was revealed, manifested by an increase in the levels of saturated, monoenoic, n-6 polyunsaturated fatty acids against the background of a deficiency of n-3 polyunsaturated fatty acids and phospholipids with an alkenyl bond – plasmalogens. It has been shown that bronchial asthma, aggravated by obesity, occurs against the background of increased synthesis of inflammatory lipid mediators – eicosanoids (thromboxane B2 and leukotriene B4). Evaluation of the correlation relationships between the studied lipids and the function of small airways revealed a high degree of relationship between their participants.Conclusion. An important pathogenetic link in the formation of small airway dysfunction in bronchial asthma aggravated by obesity is a violation of fatty acid metabolism and plasmalogen synthesis, an increase in the formation of inflammatory lipid mediators.